Body Mass Index and Edinburgh Postnatal Depression Scale Score of Pregnant Women & Breastfeeding Mothers During COVID-19 Pandemic. (14th June 2022) - Erliana, Ummu; Fly, Alyce; Xun, Pengcheng
Abstract: Objectives: A cross-sectional study was conducted to determine the association between BMI and the Edinburgh Postnatal Depression Scale (EPDS) score among pregnant women and breastfeeding mothers. Methods: An online survey was used to obtain sociodemographic data and EPDS scores from pregnant women and breastfeeding mothers in Indiana from July 27, 2020 until July 30, 2021. Potential participants were invited through a Facebook group. The inclusion criteria were pregnant women and exclusive breastfeeding mothers, 18 years of age or older, with a singleton pregnancy, who intended to breastfeed after delivery, and used English as a primary language. Data were collected using Qualtrics and descriptive statistics, including mean, standard deviation (SD) and percentages, were used to characterize demographic variables. Multiple linear regression was performed to examine the association [beta coefficient (β) with 95% confidence interval (CI)] between BMI and EPDS with adjustment for potential confounding factors (e.g., sociodemographic factors). Results: A total of 120 participants, including, pregnant women (n = 39) and breastfeeding mothers (n = 81), had a mean of age 29.69 ± 4.37 years, 93.30% described themselves as White race, 59.20% had more than 12 years to 16 years of education, 49.20% worked full time, and 32.50% had an annual income between 85, 000–149, 999. The mean EPDS score was 6.19 ± 4.14. The mean (SD) of pre pregnancy BMI (kg/m 2 ) was 27.91 ± 5.89 kg/m 2 with a range from 19.20 to 43.00. The participants with obesity had the highest mean EPDS score of 6.46 ± 4.28, followed by overweight (6.15 ± 4.42) and healthy weight (5.98 ± 3.87). After adjusting for age, employment status, education, breastfeeding and pregnancy status, and family income, BMI was not associated with EPDS score [β (95% CI) = −0.01 (−0.15, 0.12); p = 0.84). Conclusions: We found no significance association between body mass index and EPDS score of pregnant women and breastfeeding mothers. Further studies are needed. Funding Sources: Indonesia Endowment Fund for Education (LPDP).